Technical Study of Type B - Series and Kaplan Propellers with Rake Angle Variations on the Offshore Supply Vessel 80 (OSV 80) - Winarno, Arif; Hermawan, Muhammad Alif Ridha (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
The propeller is one part of the ship that is driven by the engine, which has the function of obtaining thrust for the speed of the ship so that the propeller must be able to withstand the forces acting on the blade due to hydrodynamic loads. Propellers are divided into two types, one of which is the Fixed Pitch Propeller (FPP). The speed on the ship is inseparable from a good propeller design in order to get optimal thrust generated by the propeller motion. This research was conducted because of the frequent occurrence of losses and cracks in the propeller leaves. The purpose of this study is to determine the optimum propeller thrust value from the analysis of the rake angle variation model made so that it can be seen which model variation has the highest thrust and torque values ​​and to determine the comparison of the thrust values ​​resulting from the B-Series and Kaplan model variations. This research method uses Computational Fluid Dynamic (CFD) simulations. The hypothesis from the variation simulation study that the angle influences the thrust value of the ship as well as the thrust comparison value and the flow pattern and contours is obtained from the model with the same dimensional and rotation analysis parameters and the highest efficiency value is obtained on the B-Series and Kaplan propeller models. with maximum rake angle variation.